2023
DOI: 10.3390/nu15061490
|View full text |Cite
|
Sign up to set email alerts
|

Natural Product Skatole Ameliorates Lipotoxicity-Induced Multiple Hepatic Damage under Hyperlipidemic Conditions in Hepatocytes

Abstract: Skatole (3-methylindole, 3MI) is a natural-origin compound derived from plants, insects, and microbial metabolites in human intestines. Skatole has an anti-lipid peroxidation effect and is a biomarker for several diseases. However, its effect on hepatocyte lipid metabolism and lipotoxicity has not been elucidated. Hepatic lipotoxicity is induced by excess saturated free fatty acids in hyperlipidemia, which directly damages the hepatocytes. Lipotoxicity is involved in several metabolic diseases and hepatocytes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 73 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…Coniferaldehyde can also reverse impaired glucose uptake caused by high-fat diets by upregulating GLUT2 expression [292]. Skatole, a natural compound produced by plants and intestinal microbes, improved glucose uptake and insulin resistance in HepG2 cells induced by lipotoxicity [293].…”
Section: Natural Products and Carbohydrate Metabolism In Mafld 321 Na...mentioning
confidence: 99%
“…Coniferaldehyde can also reverse impaired glucose uptake caused by high-fat diets by upregulating GLUT2 expression [292]. Skatole, a natural compound produced by plants and intestinal microbes, improved glucose uptake and insulin resistance in HepG2 cells induced by lipotoxicity [293].…”
Section: Natural Products and Carbohydrate Metabolism In Mafld 321 Na...mentioning
confidence: 99%
“…This study did not test the directionality of skatole levels and so did not postulate whether skatole was a causative agent of disease or a byproduct [ 172 ]. Skatole may be toxic at high concentrations in the body, but a recent study showed skatole may attenuate hyperlipidemic conditions of the liver [ 173 ]. Trp metabolites produced by microbes in the gut, like skatole and tryptamine, find their way to the liver through hepatic circulation and once localized, can either attenuate or exacerbate disease conditions.…”
Section: Anthranilic Acid and Beyondmentioning
confidence: 99%
“…Numerous studies have shown that palmitic acid (PA), the most abundant saturated FFA in circulation, triggers excessive reactive oxygen species production due to disrupting mitochondrial function and inducing oxidative stress, which has been implicated in the pathogenesis of IR associated with the endoplasmic reticulum (ER) stress [4]. In addition, ER stress and the subsequent unfolded protein response (UPR) also have been implicated in the impaired insulin signaling in hepatocytes caused by PA [5][6][7].…”
Section: Introductionmentioning
confidence: 99%